Women in STEM Education Research, 2006-2025: Knowledge Evolution, Global Collaboration, and SDG Alignment - Prakoso, Albrian Fiky; RoziqiFath, Zain Fuadi Muhammad; Ghofur, Muhammad Abdul; Nurlaili, Eka Indah; Rafsanjani, Mohamad Arief; Kurniawan, Riza Yonisa; Srisuk, Prattana (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This bibliometric study maps the development of research on women in STEM education using 348 Scopus-indexed, English-language, open-access publications spanning 2006-2025. Bibliographic records were retrieved on June 12, 2025, and analyzed using Biblioshiny through performance analysis, keyword co-occurrence, co-authorship, co-citation, thematic mapping, and historiographic analysis. The field recorded an annual growth rate of 14.45%, with publication output increasing markedly after 2015 and remaining high after 2020. PLOS ONE was the most productive source, followed by CBE-Life Sciences Education and Sustainability, while highly cited publications by Stoet and Geary and Dennehy and Dasgupta formed important intellectual foundations for research on gender disparities, mentoring, and institutional intervention. Collaboration was extensive: 313 of the 348 documents (89.9%) were multi-authored, and 97.8% of authors contributed to co-authored publications. However, 76% of the scholarly output originated from the Global North, indicating persistent geographical imbalance. Conceptual mapping identified a pedagogical cluster centered on education, gender, students, mathematics, and engineering, alongside a demographic and indexing cluster dominated by female, male, human, and adult. The analysis also revealed limited attention to technology education, intersectional perspectives, and Global South contexts. Overall, the literature is substantively aligned with SDGs 4 and 5 through its focus on equitable access, participation, retention, and institutional inclusion. The findings support more reciprocal North-South partnerships, context-sensitive intervention studies, and stronger integration of intersectional and technology-focused research.